RESEARCH STUDIES IN DIGITAL ACCOUNTING: AN ANALYSIS FROM INCEPTION - Indrayani; Eko Ganis Sukoharsono; Wuryan Andayani; Ali Djamhuri (RADJA PUBLIKA, 2024)
The long-term effects of accounting studies are related to digital accounting. Bibliographic evaluations haven't given much thought to how the literature on digital accounting has developed, nevertheless. A comprehensive summary of the evolution and advancement of the literature on digital accounting, based on the whole citation network, is given by several research reviews. The study investigates three areas: created and shared in research on digital accounting, subjects related to digital accounting covered in research on digital accounting, and qualities of digital accounting do writers in digital accounting research from different nations possess. 84 publications that were published between 2005 and 2023 and found in the Scopus database served as the basis for this bibliometric analysis. These results show that the first publications on digital accounting were books that were indexed by Scopus. These books covered fundamental subjects like accounting software, XBRL (eXtensible Business Reporting Language), and EDI, and they laid the groundwork for the field's subsequent development and dissemination. Despite this, the majority of publications on digital accounting concentrate on the same areas, such as business, management, accounting, computer science and economics, economics, and finance. The most popular subjects are blockchain, information technology, digital economy, accounting systems, accounting information, learning systems, e-learning, and digital technologies.